SPOR BİLİMLERİ FAKÜLTESİ REKREASYON BÖLÜMÜ ÖĞRENCİLERİNİN HEDONİK (HAZCI) TÜKETİM DAVRANIŞLARININ İNCELENMESİ - AKSUNGUR, BÜNYAMİN (Fırat Üniveristesi, 2023)
Fırat Üniversitesi Spor Bilimleri Fakültesi Rekreasyon Bölümü Öğrencilerinin Hedonik (Hazcı) Tüketim Davranışlarının İncelenmesi amaçlanmıştır. Bu araştırmanın evreni 2021-2022 eğitim–öğretim döneminde Fırat Üniversitesi Spor Bilimleri Fakültesinde öğrenin gören öğrenciler oluşturmaktadır. Araştırmanın örneklemi ise, Fırat Üniversitesi Spor Bilimleri Fakültesi içerisinde öğrenim gören N=194 Rekreasyon Bölümü öğrencileri oluşturmaktadır. Bu öğrencilerden 166'si anketleri araştırmaya uygun bulmuş ve değerlendirmeye alınmıştır. Çalışmaya katılma şartları; kolayda örnekleme metoduyla seçilmiş kişilere sorularak, gönüllü onam formunu okutularak ve imzalamasının ardından, 6 Soruluk kişisel bilgi formu ile "Hedonik Tüketim Ölçeği" doldurulmuştur. Anket formu iki temel bölümden oluşmaktadır. İlk bölüm 6 soruluk demografik bilgilerden oluşmaktadır. İkinci bölümde, Arnold ve Reynold'un geliştirdiği hedonik tüketim ölçeği kullanılmıştır. Bulgulara bakıldığında kadın öğrencilerin erkek öğrencilere göre daha fazla hedonik tutum sergiledikleri bulunmuş, yaş ilerledikçe hedonik tutumun değerlerini yükseldiği saptanmıştır. Sonuç olarak; Spor Bilimleri Fakültesi Rekreasyon Bölümü Öğrencilerinin Hedonik (Hazcı) Tüketim Davranışlarının İncelenmesinde, kadın öğrencilerin kendilerini alışveriş yaparken değer elde etmek yani bir ürünü başkalarının aldığından daha ucuza alarak veya pazarlık yaparak haz almak ve sosyalleşmek yani arkadaşlar ve aileler ile bağ kurarak hedonik tutum sergilemek ve yaş ilerledikçe daha fazla hedonik tutum içinde bulunmak, ve genellikle diğer elde etmek, başkalarını mutlu etmek ile fikir edinmek yani yeni trendlerden haberdar olmak ve tüketime yön vermek amacıyla hedonik tutum sergiledikleri ve haz aldıkları sonucuna ulaşılmıştır. Anahtar Kelimeler: Rekreasyon, Hedonik Tüketim, Haz Alma, Alışveriş

It is aimed to investigate the Hedonic Consumption Behaviors of Fırat University Faculty of Sport Sciences Recreation Department Students. The universe of this research consists of students studying at the Faculty of Sport Sciences at Fırat University. The sample of the study consists of students of the Recreation Department (194) studying at the Faculty of Sports Sciences of Fırat University. Among these 194 students, 166 students were reached and the questionnaires were filled. Conditions of participation in the study; The "Hedonic Consumption Scale" was filled with a 6-question personal information form, after asking the people selected by convenience sampling method, reading and signing the voluntary consent form. The questionnaire form consists of two main parts. The first part consists of demographic information with 6 questions. In the second part, a 23-item scale including the reasons for hedonic consumption was used. The 23 questions belonging to the second part were prepared in the form of a 5-point Likert scale (1: strongly disagree, 2: disagree, 3: neither agree nor disagree, 4: agree, 5: strongly agree) using the scale developed by Arnold and Reynold (2003) . This scale consists of 6 sub-dimensions. When the findings were examined, it was found that female students exhibited more hedonic attitudes than male students, and it was determined that the values of hedonic attitude increased as the age progressed. In conclusion; In the Examination of Hedonic (Hedonic) Consumption Behaviors of the Students of the Faculty of Sport Sciences, Recreation Department, it was aimed that female students gain value while shopping, that is, to get pleasure by buying a product cheaper than others or bargaining and socializing, that is, to show a hedonic attitude by connecting with friends and families and to develop a hedonic attitude as the age progresses. It has been concluded that they display a hedonic attitude and take pleasure in order to have a more hedonic attitude, and generally to get others, to make others happy, to get ideas, that is, to be aware of new trends and to direct consumption. Keywords: Rekreasion, Hedonic Consumption, Enjoyment, Shopping
Investigation of hedonic (hazci) consumption behaviors of sports sciences faculty recreation department students
Keywords: Spor